Comparison of Soil Arthropod Diversity and Community Structure in Various Types of Land Cover in Malang Region, East Java, Indonesia - Yanuwiadi, Bagyo; Suharjono, Suharjono; Kurniawan, Nia; Fathoni, Muhammad; Nurrofik, Agus; Assiddiqy, Miftah Farid; Shahroni, Abdul Mutholib (Journal of Tropical Biodiversity and Biotechnology, 2023)
Land cover heterogeneity can affect the structure of biodiversity in the supplied niche, so it is necessary to know the taxa community. This study aimed to understand the effect of land cover variation on the diversity and community structure of soil arthropods. The types of habitats used include urban areas, agroforestry, gardens, and natural forests which are determined in the Malang Region, East Java, Indonesia. Hand sorting and hay bait traps were applied in this study to obtain a variety of arthropod soils and the Berlese-Tullgren funnel was used to extract them. As a result, there are 25 families from 15 orders collected based on their ecological roles. The abundance of Philoscidae in sites S1 and S2 (urban green space), Talitridae in site S6 (agroforestry), and Isotomidae in sites S3, S4, and S5 (highland mixed forest) was highest and dominant. Site S7 has the highest diversity (H' = 2.56; 1-D = 0.90; J' = 0.76) even though its family richness is lower. The site S3 counter-site had relatively high taxa richness (TR = 13), but low diversity (H' = 1.02; 1-D = 0.39; J' = 0.16). Based on clustering analysis and NMDS ordination, 3 classifications of habitat types were obtained, namely I (S6 & S7), II (S3, S4 & S5), and III (S1 & S2). Mixed forest habitats contain a more complex diversity of soil arthropods, which can serve as a model for improving the fertility of disturbed ecosystems.